The Influence of Brand Awareness, Brand Personality, Perceived Quality, and Perceived Value on Brand Loyalty with Customer Engagement as a Mediating Variable in the Cosmetics Industry in the Digital Era (A Case Study of the Make Over Brand) - Trisya Afrilya Suryadi; Mahir Pradana; Nurafni Rubiyanti (JOURNAL OF HUMANITIES, SOCIAL SCIENCES AND BUSINESS, 2026)
Rapid developments in digital technology and the widespread use of social media have fueled substantial growth in Indonesia’s cosmetic sector. With local and foreign brands competing intensely, companies are under constant pressure to reinforce customer allegiance. The central purpose of this research is to examine the connections between Brand Awareness, Brand Personality, Perceived Quality, and Perceived Value and Brand Loyalty, as well as to test whether Customer Engagement plays a mediating role, specifically among Make Over users. Using a quantitative methodology and a cross-sectional framework, the study collected primary data through questionnaires distributed to 384 respondents who were Make Over customers and had been exposed to social media campaigns or reviews. The sample was obtained using purposive sampling. Analysis via PLS-SEM with SmartPLS 4.1 indicates that each of the four predictor variables positively and significantly affects both Brand Loyalty and Customer Engagement. The model explains 57.0% of the variance in Brand Loyalty (R² = 0.570) and 52.2% of the variance in Customer Engagement (R² = 0.522). In addition, Customer Engagement exhibits a positive and significant impact on Brand Loyalty and effectively mediates the paths connecting all four independent variables to Brand Loyalty. These findings indicate that customer loyalty in the digital cosmetic industry is shaped not only by brand equity dimensions and product quality, but also by the company’s ability to establish meaningful interactions and encourage active customer engagement across digital platforms.